The Ulnar Collateral Ligament Responds to Stress in Professional Pitchers. Issue 7 (31st July 2020) - English, Joy; Cushman, Daniel; Zhang, Chong; Presson, Angela; Yoon, Steve; Schulz, Brian; Li, Bernard; Chalmers, Peter
Objectives: It remains unknown whether the frequently injured ulnar collateral ligament (UCL) responds to the stress of baseball pitching. Our purpose was to determine the response of the UCL in professional pitchers to pitching and rest. Methods: In a prospective study supported by Major League Baseball, all pitchers within a single professional baseball club were enrolled. Surgical and pitching history were recorded. An ultrasound (US) of the ligament was then performed by a single fellowship-trained ultrasonographer with extensive UCL US experience at the beginning of the season (T1), the end of the season (T2), and the beginning of the following season (T3). We measured UCL thickness and ulnotrochlear joint opening at 30° of flexion with and without valgus stress. Two US images were saved. Inter- and intra-rater reliability were determined. A multivariable analysis was conducted. Results: 185 total pitchers were included: 94 pitchers at T1, 83 at T2, and 118 pitchers at T3. Excluding player movement, follow-up rate was 70% between T1 and T2 and 91% between T2 and T3. These pitchers were 23 [21, 25] years old (median [inter-quartile range]), had 12 [7, 15] years pitching experience, and had peak velocity of 95 [93, 97] miles per hour. Intra- and inter-rater reliability was excellent. Baseline UCL thickness was associated with peak velocity (p=0.031) and prior UCL reconstruction (UCLR, p=0.024). After accounting for years of pitching experience, peak velocity and time, UCL thickness was greater in those with prior UCLR (p<0.001). After accounting for pitching experience, peak velocity, and prior UCLR, thickness increased during the season (p=0.002) and decreased during the offseason (p=0.001). After accounting for these same variables, valgus laxity at 30° increased during the season (p=0.002) and decreased during the off season (p=0.029). Conclusion: The ulnar collateral ligament responds to stress in professional pitchers by becoming thicker and more lax and to rest by becoming thinner and less lax.